Peran Indeks Massa Tubuh, Kadar Hemoglobin, dan Status Pendidikan Ibu terhadap Berat Badan Lahir Bayi: Tinjauan Literatur - Nabila Athifa Puspadewi; Fiona Paramitha (Jurnal Anestesi, 2026)
Low birth weight (LBW) remains a significant global health issue contributing to high infant morbidity and mortality rates. Maternal factors such as body mass index (BMI), hemoglobin levels, and maternal education status play crucial roles in determining neonatal birth weight. This study aims to analyze the relationship between BMI, hemoglobin levels, and maternal education status on infant birth weight through a literature review approach. The method employed was a literature review by searching scientific articles from Google Scholar, PubMed, and ScienceDirect databases within the 2016–2026 period. Inclusion criteria included full-text research articles relevant to the topic, utilizing both quantitative and qualitative study designs. The findings indicate that low maternal BMI is associated with an increased risk of LBW due to inadequate nutritional intake during pregnancy, while low hemoglobin levels (anemia) contribute to impaired oxygen supply to the fetus. Additionally, low maternal education status affects health literacy and access to antenatal care, indirectly increasing the risk of LBW. Overall, these three factors are interrelated in influencing infant birth weight. Therefore, comprehensive interventions through improving nutritional status, preventing anemia, and enhancing maternal health education are essential strategies to reduce the incidence of LBW.